Cognitive modeling of company auditors - Fung, Chorng Yuan (Universiti Malaysia Sarawak, UNIMAS, 2010)
Cognitive task analysis is the preliminary stage in the design and development of a training programme. The purpose of this research is to carry out cognitive task an alysis of expert company auditors using Think Aloud method. The results of the analysis will enable the construction of cognitive models of expert auditors. Utilising the models will enable training professionals to design effective training programmes for the novice auditors. The purpose is to provide an avenue for the novice auditors to understand the knowledge and cognitive processes of expert auditors and therefore to improve theirs for better performance.